تقنيات التمويل قصيرة الأجل للصادرات - شربي, محمد الأمين (Sciences humaines, 2016)
إن تنمية الصادرات تعتبر ضرورة حتمية لاقتصاد كل دولة، وهذا نظرا لما تلعبه هذه الصادرات من دور هام في الاقتصاديات المعاصرة، لما لها من آثار إيجابية على الميزان التجاري ومن ثم ميزان المدفوعات، فضلا عن الدخل الوطني الإجمالي للدولة.ومن خلال هذا يتبين لنا مدى أهمية تطوير وترقية الصادرات والدفع بعجلة التصدير، وذلك من خلال غزو الأسواق الخارجية، ولا يتأتى هذا إلا من خلال تحفيز المصدرين والمؤسسات المصدرة للدخول في التصدير، وهذا بتصميم سياسات وحوافز نجد من بينها سياسات تمويل الصادرات، وبخاصة سياسات التمويل قصيرة الأجل، ولا يمكن اعتبار هذه الأخيرة ناجحة وناجعة إلا إذا جعلت من مصلحة المنتج المحلي أن يتوجه بإنتاجه إلى التصدير بدلا من السوق المحلي.ومن هنا يبرز الدور الذي يمكن أن تلعبه البنوك والمؤسسات المالية، وهذا بتوفيرها للمصدر والمستورد على حد سواء قروض تشجيعية وتحفيزية لتمويل الصادرات، هذه الأخيرة ستسمح من دون أدنى شك من إنجاح العملية التصديرية. الكلمات المفتاح: تمويل الصادرات، ترقية الصادرات، التمويل قصير الأجل للصادرات، التمويل قصير الأجل، المؤسسات المالية.   The development of exports is considered to be a necessity for the economy of every country. These exports play a significant role in contemporary economics because of their effect on the trade balance, balance of payments, as well as the Gross National Income.The exports have imposed themselves on the international economy, especially as a result of the changes in the economic fields regarding the application of the regulations of the World Trade Organization on one hand, and facing the regional economic blocs on the other.Therefore, we can see clearly the importance of development and advancement of exports which may be done by opening new foreign markets of export, a process that cannot be made without supporting the exporters and the establishments concerned with exporting products, which can be achieved through designing new policies and incentives such as financing the exports.The financing of exports method cannot be useful and beneficial unless it focuses on the export of national products instead of local consumption, which implies that a major role must be played by the banks and financial institutions which have to provide financial loans that would encourage financing of exports to both exporters and importers, and eventually will lead to the success of exporting